GOVERNMENT COMMUNICATION THROUGH HASHTAG #ENERGIBERKEADILAN IN THE SOCIAL MEDIA OF THE MINISTRY OF ENERGY AND MINERAL RESOURCES - Ramadani, Thoriq (Jurnal Administrasi Negara, 2019)
This research aims to determine government communication through the hashtag #EnergiBerkeadilan on social media Ministry of Energy and Mineral Resources (EMR). Research with a qualitative approach with a case study method on social media Ministry of EMR, d ata collection techniques with primary and secondary data. Primary data from interviews with key informants and secondary data in the form of literature reviews such as journals, books and related regulations. The results of the research revealed that the hashtag #EnergiBerkeadilan is a summary of Article 33 of the 1945 Constitution and President Joko Widodo’s Nawa Cita, which is a tagline from the Ministry of EMR and is continued to become a hashtag on social media of the Ministry of EMR. The hashtag #EnergiBerkeadilan (1) was considered not to change how we spoke verbally or non-verbally on social media, (2) it became a campaign related to programs and performance achievements of the EMR sector on social media Ministry of EMR, (3) it could be used or made content search sources, (4) require activities that are planned and carried out broadly, to become a new means of social networking hashtag #Energiberkeadilan which makes people interested in participating in these activities, and (5) the Ministry EMR regularly carries out Temu Netizen activities, to change how build virtual communities.